Synthesis of Acetyl-oxy Phthalimide Derivatives of Diphenyl Amine as Potential Antibacterial - Rajora, Sonal; Banu, Tahira; Khatri, Dilip; Talesara, G.L. (Asian Journal of Chemistry, 2010)
Acetyl-oxy phthlimide derivatives of diphenyl amine are synthesized and screened for their antibacterial activity.